(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Geopolymer materials have garnered significant attention as sustainable alternatives to traditional Portland cement-based materials. This study explores the effect of various curing regimes on the compressive strength (at 7 and 28 days) and flexural strength (at 28 days) of geopolymer mortars composed of fly ash (FA) and metakaolin (MK) in varying proportions. Four mixes were used: 100% FA; 60% FA+ 40% MK; 50% FA+10% OPC+ 40% MK; and 100% OPC. The binders were activated using 15% sodium silicate (solid content) with an alkali modulus (Ms = SiO2/Na2O) equal to 1. The curing conditions included ambient curing and elevated temperature curing at 80 °C under different setups. The results demonstrate that the curing regime significantly influences the mechanical properties of alkali-activated mortars (AAMs). Where, the results showed that heat curing regime enhanced the flexural, early-age compressive strength and the microstructure, in comparison with other regimes. The findings provide valuable insights into optimizing curing practices for geopolymer mortars to achieve desired mechanical properties. Replacing 40% of fly ash with metakaolin improved the microstructure of the matrix and decreased micro-cracks.